NUMERICALLY PREDICTING SETTLEMENTS OF WASTE COCONUT FIBER (WCF) MIXED FLEXIBLE PAVEMENT IN HOMOGENEOUS SANDY SOIL BY USING PLAXIS 3D - Md. Foisal Haque (International Journal of Civil Engineering and Infrastructure, 2021)
Surface settlement of flexible pavement in coastal reason occurs for the movement of heavy vehicle, liquefaction of soil layer during seismic shaking, land sliding etc. In coastal area, surface settlement is higher than other geographical area because several sandy layers present in the coastal reason. Surface settlement disturbs the longevity of flexible pavement in homogeneous sandy layer. Waste coconut fiber (WCF), fly ash, coir etc. are suitable additives for reducing such types of settlement. In the present study, numerical analysis performs PLAXIS 3D and various (5, 10, 15, 20, 25) percentages of WCF mix with the asphalt by weight for reducing surface settlement of flexible pavement. Mohr-Coulomb failure criterion uses in the numerical analysis and liquefaction has not considered in the present study. However, WCF increases elastic modulus of flexible pavement and it reduces settlement of the pavement. Minimum surface settlement occurs at the maximum percentage of WCF and it is 1.68mm. Therefore, mixer of WCF protects the flexible pavement against severe damage.